How Do Family Physicians Perceive Their Role in Providing Pre-exposure Prophylaxis for HIV Prevention?–An Online Qualitative Study in Flanders, Belgium - Vanhamel, Jef; Reyniers, Thijs; Wouters, Edwin; van Olmen, Josefien; Vanbaelen, Thibaut; Nöstlinger, Christiana; Mieghem, Heleen Van; Landeghem, Ella Van; Rotsaert, Anke; Laga, Marie; Vuylsteke, Bea (Frontiers in Medicine, 2022)
Introduction: In Belgium, the provision of pre-exposure prophylaxis (PrEP) for HIV prevention is centralized in specialized HIV clinics. Engaging family physicians in PrEP care could help scale-up its delivery and reach underserved populations. The objective of this study was to gain insight into family physicians’ self-perceived roles in providing PrEP. Methods: We conducted 16 online group discussions with a total of 105 Flemish family physicians, between November 2020 and February 2021. A brief online questionnaire assessed their socio-demographics and experience with sexual health. We analyzed verbatim transcribed data using a grounded theory approach. Results: Despite limited awareness and experience, participants reported a high willingness to be more actively involved in PrEP care. Four potential roles for the family physician in PrEP care were identified: acting as low-threshold entry point for advice; opportunistic case finding of PrEP candidates; initiating appropriate care for PrEP-eligible clients; and ensuring high-quality follow-up care for PrEP users. Participants framed each of these roles within their current activities and responsibilities as primary care providers. Yet, participants differed in their views on the concrete operationalization of these roles, and in the extent of their involvement in PrEP. Particular challenges were a lack of experience with antiretrovirals, perceived limited exposure to clients at high HIV risk, and a lack of expertise and resources to conduct time-intensive risk assessments and counseling related to PrEP. Conclusion: Belgian family physicians demonstrated a keen willingness to be involved in PrEP care, but had differing views on the practical implementation into their practices. Providing tailored training on sexual health and PrEP, and investing in collaboration between primary and secondary care, could optimize the integration of PrEP in the primary care practice.